PATHOPHYSIOLOGY OF SECONDARY COMPLICATIONS OF DIABETES MELLITUS - Prabhakar, Pranav Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Diabetes mellitus (DM) is the most common endocrine metabolic disorder, characterised by hyperglycemia. The cause of this hyperglycemia is either insufficient or inefficient insulin which leads to the imbalance in the metabolism of not only carbohydrates but also protein and lipids. Diabetes mellitus is associated with various kind of abnormalities which affects almost all the parts of the body including eye, kidney, brain, foot etc. Hyperglycemia is not the only reason which gives diabetes mellitus a tag of most apocalyptic disease; it is the complications which arise from the higher concentration of glucose or metabolites comes from its variant metabolic pathways. DM causes both microvascular and macrovascular complications. Microvascular complications, caused by the damage of small blood vessels, includes nephropathy (kidney disease), retinopathy (eye damage) and neuropathy (nerve damage) whereas macrovascular complication, caused by the damage of large blood vessels, includes blood vessels arteries and veins. There are six metabolic pathways are there which normally leads to these complications. These pathways are sorbitol pathway, advanced glycation pathway, Hexosamine pathway, PKC pathway, ketoaldehyde pathway and oxidative stress.